Preparation and nutritional properties of xylooligosaccharide from agricultural and forestry byproducts: A comprehensive review - Yan, Feng; Tian, Shuangqi; Du, Ke; Xue, Xing'ao; Gao, Peng; Chen, Zhicheng (Frontiers in Nutrition, 2022)
Xylooligosaccharide（XOS）are functional oligosaccharides with prebiotic activities, which originate from lignocellulosic biomass and have attracted the extensive attention from scholars in recent years. This paper summarizes the strategies used in the production of XOS, and introduces the raw materials, preparation methods, and purification technology of XOS. In addition, the biological characteristics and applications of XOS are also presented. The most commonly recommended XOS production strategy is the two-stage method of alkaline pretreatment and enzymatic hydrolysis; and further purification by membrane filtration to achieve the high yield of XOS is required for prebiotic function. At the same time, new strategies and technologies such as the hydrothermal and steam explosion have been used as pretreatment methods combined with enzymatic hydrolysis to prepare XOS. XOS have many critical physiological activities, especially in regulating blood glucose, reducing blood lipid, and improving the structure of host intestinal flora.